Population Genetic Structure of Convolvulus persicus L. in the Western Black Sea Region (Romania and Bulgaria) and Its Restricted Distribution - Elena Monica Mitoi; Carmen Maximilian; Irina Holobiuc; Daniela Mogîldea; Florența-Elena Helepciuc; Claudia Biță-Nicolae (Ecologies)
Convolvulus persicus L. is an endangered narrow-range taxon, characteristic of the habitats along the coastal regions of the Caspian and the Black Seas. The aims of our research were to update the actual distribution area and the genetic evaluation of three representative populations from the western coastline of the Black Sea located in Sulina, Agigea, and Durankulak. ISSR amplifications were used to assess the genetic intrapopulation diversity and the genetic differentiation among populations. The average genetic polymorphism was 57.8 ± 16.03%. The intrapopulation genetic diversity parameters indicated that the Agigea population exhibits a higher genetic diversity, with this small population being part of the Agigea Marine Dunes Reserve. Although the interpopulation genetic distance was reduced (0.176–0.223) and the distribution of the total variation (AMOVA) was 57% within the population and 43% among the populations, the interpopulation genetic differentiation (PhiPT) was high (0.428, p < 0.001), probably due to the large geographical distances between the remaining populations. The populations’ genetic structures showed a lower genetic distance between the Agigea and Sulina samples. The clonability test supported the vegetative multiplication on the Durankulak and Sulina beaches. Our results showed that the genetic diversity and the distance among the populations in C. persicus were influenced by habitat conditions, destruction, and fragmentation, but also by conservation measures.